2017
DOI: 10.3390/ijms18102073
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Circulating Type II Collagen Degradation Marker (CTx-II) Are Associated with Specific VDR Polymorphisms in Patients with Adult Vertebral Osteochondrosis

Abstract: Both vitamin D and collagen have roles in osteocartilaginous homeostasis. We evaluated the association between the circulating 25-hydroxyvitamin D (25(OH)D), type I and II collagen degradation products (CTx-I, and CTx-II), and four vitamin D receptor gene (VDR) polymorphisms, in Italian males affected by low back pain (LBP) due to herniation/discopathy and/or vertebral osteochondrosis. FokI, BsmI, ApaI, and TaqI VDR-polymorphisms were detected through PCR–restriction fragment length polymorphism (RFLP), and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…These pieces of evidence suggest that calcitriol, at the pharmacological concentration used in this study, has a general anti-proliferative and catabolic effect on disc cells. For these reasons, the use of vitamin D to treat the degenerated disc with homeostatic or regenerative purposes is not suggestable, particularly for patients bearing FF VDR genotype which showed the highest risk of developing degenerative disc diseases [ 7 , 8 , 12 ]. Nevertheless, cells bearing the Ff genotype were the most responsive to the vitamin D supplementation, showing anti-inflammatory and catabolic behaviors in response to the treatment with the hormone, likely related to matrix remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pieces of evidence suggest that calcitriol, at the pharmacological concentration used in this study, has a general anti-proliferative and catabolic effect on disc cells. For these reasons, the use of vitamin D to treat the degenerated disc with homeostatic or regenerative purposes is not suggestable, particularly for patients bearing FF VDR genotype which showed the highest risk of developing degenerative disc diseases [ 7 , 8 , 12 ]. Nevertheless, cells bearing the Ff genotype were the most responsive to the vitamin D supplementation, showing anti-inflammatory and catabolic behaviors in response to the treatment with the hormone, likely related to matrix remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a correlation between the aforementioned genetic variants and specific lumbar spine pathologies, such as herniation, discopathy, and osteochondrosis, has been observed [ 7 , 8 , 9 , 10 ]. Some VDR alleles and genotypes predisposed to lumbar spine pathologies have been identified in patients with a concomitant increase of type II collagen degradation products, which likely derives from the degradation of the disc’s matrix [ 11 , 12 ]. However, there are still few findings concerning the contribution of these variants to pathologic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Adult NP cells represent a kind of cartilage-like cells, mainly characterized by the expression of type II collagen [13]. Type II collagen is one of the most important collagen components in the intervertebral disc, also known as cartilage collagen, which is mainly found in cartilage and intervertebral disc nucleus [14]. Sive et al [15] have confirmed by in situ hybridization that the expression of type II collagen in the NP cells of the intervertebral disc gradually decreases with the progression of degeneration [15].…”
Section: Effects Of Agomirna-222 Transfection On Hnpc Cellsmentioning
confidence: 99%
“…W grupie pacjentów, jaką stanowili mężczyźni leczeni z powodu bólów lędźwiowych kręgosłupa spowodowanych przepukliną, dyskopatią bądź chorobą Scheuermanna (jałową martwicą kręgosłupa), również zaobserwowano występowanie poszczególnych odmian polimorficznych genu VDR [61]. Analizie poddano genotypy Apa1, Fok1, Bsm1 i Taq1, stężenie cholekalcyferolu oraz produktów degeneracji kolagenu typu I i II.…”
Section: Wpływ Polimorfizmów Genu Receptora Witaminy D (Vdr) Na Układunclassified
“…U pacjentów z polimorfizmem FF i Ff w porównaniu do osób z polimorfizmem ff, stwierdzono niższe stężenie cholekalcyferolu, sugerujące występowanie większych niedoborów witaminy D u nosicieli alleli F. Wyższy katabolizm kościo-chrzęstny opisano natomiast u nosicieli alleli T (genotyp TT >Tt>tt). Potwierdzono swoiste cechy genotypowe i biochemiczne wskazujące na rolę witaminy D w utrzymaniu homeostazy kościo-chrzęstnej (osteocartilaginoushomeostasis) poprzez zwiększone zużycie witaminy D i zwiększony katabolizm chrząstek [61].…”
Section: Wpływ Polimorfizmów Genu Receptora Witaminy D (Vdr) Na Układunclassified